2017
DOI: 10.1139/cjpp-2016-0303
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine attenuates lipopolysaccharide-induced inflammatory responses through upregulation of USP25

Abstract: Lipopolysaccharide (LPS) is a key pathogenic factor in sepsis, and its recognition by toll-like receptor 4 (TLR4) can activate two district signaling pathways, leading to activation of transcription factors including NF-κB and interferon regulatory factor 3 (IRF3). Chloroquine (CQ) has been shown to affect LPS-TLR4 colocalization and inhibit both MyD88-dependent and TRAM/TRIF-dependent pathways, though the mechanism involved is still poorly understood. Here, we found that the ubiquitin-proteasome system might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…We assumed that LPS may increase USP25 protein level to stabilize HBO1 via enhancing HBO1 deubiquitination. As predicted, LPS increased USP25 protein level in a time-dependent manner in THP-1 cells, consistent with other reports [23, 35] (Fig. 5A).…”
Section: Resultssupporting
confidence: 93%
“…We assumed that LPS may increase USP25 protein level to stabilize HBO1 via enhancing HBO1 deubiquitination. As predicted, LPS increased USP25 protein level in a time-dependent manner in THP-1 cells, consistent with other reports [23, 35] (Fig. 5A).…”
Section: Resultssupporting
confidence: 93%
“…We conclude that increased intestinal permeability indicates impaired barrier function and that increased uncontrolled passage of substances through the barrier causes increased inflammatory responses [33]. Indeed, RAPA-treated piglets with disrupted intestinal integrity showed higher levels of pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, compared to the control treatment.…”
Section: Discussionmentioning
confidence: 76%
“…These effects may contribute to the alleviation of the weaning stress response in piglets. The results from previous studies showed CQ promoted injury recovery by preventing the degradation of the autophagic and ubiquitinated protein and inhibiting autophagy-associated inflammation [33,35].…”
Section: Discussionmentioning
confidence: 97%
“…USP25 deficient mice have been shown to be more susceptible to virus infection and LPS-induced septic shock [63,65].IL-17-mediated inflammation is also attenuated by USP25 through TRAF5 and TRAF6 deubiquitination [66]. The anti-malarial drug chloroquine is suggested to alleviate LPS-induced inflammation by up regulatingUSP25 in macrophages [125].…”
Section: Uspsmentioning
confidence: 99%